A New Approach to Unauthorized Contract and Its Comparison to Iranian Civil Code - Sajjad Davarpanah Moghaddam; Hosein Saberi; Hosein Naseri Moghaddam (پژوهش‌نامه حقوق اسلامی, 2023)
Imamiya jurisprudence has formed the main foundations of the Iranian Code of Civil. Based on this dependence, the basic and general views of the Code of Civil and, accordingly, some of the opinions of legal scholars are derived from jurisprudential opinions. One of these opinions is the definition that has been provided for unauthorized contracts. Imamiya jurists consider any contract in which an unauthorized person has dealt the property of the owner as an ‘unauthorized contract’ and becomes valid and enforceable by the owner. The same approach has been considered as a certain and undeniable affair in the Civil Code, and accordingly, Iranian legal scholars have also acknowledged this definition of unauthorized contracts. The investigation made in relevant narrations and custom, shows that an unauthorized contract can be declared valid and enforceable only in a situation where the unauthorized person does not have any possibility to communicate with the owner to obtain his permission. In this case, if he makes the contract in good faith and with an intention to gain benefit for the owner, provided that he has a deep friendship or tie with the owner, or is an agent on his behalf and without trespassing the scope of his authority, this unauthorized contract can be declared valid and enforceable by the Owner.